Antimicrobial peptides engineering and their immobilization studies for catheter coating development - Lim, Kaiyang (2015)
With rapid rise in the frequency of nosocomial infections, there is an increasing demand for biomedical devices with good antimicrobial properties. Antimicrobial peptides (AMPs), which possess excellent bactericidal potency and biocompatibility properties, are promising antimicrobial coating agents for immobilization onto biomedical device relevant surfaces. The AMP’s membrane-permeabilizing mechanism of action renders it more difficult for pathogens to develop resistance. In the first part of this Ph.D. research project, an arginine-, tryptophan-rich synthetic peptide (CWR11) with potent broad-spectrum antimicrobial activity and salt resistance properties was engineered to be used as a model AMP candidate for subsequent antimicrobial surface functionalization studies. To investigate if immobilization compromises the AMP’s stability and antimicrobial property, two immobilization platforms were developed to graft CWR11 onto model polymethylsiloxane (PDMS) surface. The first platform utilizes an allyl glycidyl ether (AGE) polymer brush-based tethering chemistry while the later platform focuses on the use of a polydopamine (PD)-based surface functionalization strategy. A variety of surface characterization assays confirmed the successful grafting of AMPs onto the functionalized PDMS surface via both immobilization strategies. Surface antimicrobial assay and cytotoxic investigation confirmed that the CWR11-immobilized surfaces, from both immobilization platforms, have bactericidal and anti-biofim properties, and are also non-cytotoxic to mammalian cells. The simple immobilization strategy, enhanced peptide grafting efficacy and gentler treatment conditions makes the PD-based immobilization platform a more attractive choice for subsequent translational studies onto commercial silicone catheters. AMP-immobilized catheters, using the PD-based immobilzation platform, illustrated similar antimicrobial potency, as well as good long term stability retaining their biocidal potency when exposed to a variety of solvent conditions and prolonged soft cleaning condition. Contact active catheters developed in the first section, however, are ineffective in targeting planktonic bacteria, which can proliferate in the surrounding environment, eventually overcoming the immobilized AMP rendering them ineffective. To address this challenge, a subsequent study was initiated to formulate a controlled release polymeric coating that can provide localized, sustained AMP delivery to the target site. A dual-layered assembly (PCL(P)-POPC(P)) consisting of an AMP-impregnated basal PCL matrix layered with a thin POPC film to modulate release, was developed. This coating exhibited excellent sustained peptide release up to 30 days. Peptide characterization assays demonstrated conservation of the encapsulated AMP’s (HHC36) structural integrity and antimicrobial functionality. PCL(P)-POPC(P)-coated catheters demonstrated potent antimicrobial and anti-biofilm activity against multiple UTI-relevant bacterial strains. The controlled and sustained release of AMP also prolonged bactericidal properties, retaining good antibacterial properties when subjected to multiple bacteria exposures. In conclusion, this thesis presents proof-of-concept studies of the application of short AMPs as antimicrobial coating agents on urinary catheter. The successful engineering a potent, broad spectrum synthetic AMP and its successful application in the respective catheter antimicrobial coating development demonstrates the feasibility and potential of an AMP-based antimicrobial urinary catheter in treating or preventing CAUTI. The outcomes of this thesis now opens the way for further optimization of AMP-impregnated devices that can effectively prevent and/or treat bacterial infection while minimizing the risks of evoking pathogen resistance.